Impact of COVID-19 outbreak on the mental health in sports: a review - Shukla, A.; Dogra, D. K.; Bhattacharya, D.; Gulia, S.; Sharma, R. (Sport Sciences for Health, 2023)
Global pandemic, lockdown restrictions, and COVID-19 compulsory social isolation guidelines have raised unprecedented mental health in the sports community. The COVID-19 pandemic is found to affect the mental health of the population. In critical situations, health authorities and sports communities must identify their priorities and make plans to maintain athletes` health and athletic activities. Several aspects play an important role in prioritization and strategic planning, e.g., physical and mental health, distribution of resources, and short to long-term environmental considerations. To identify the psychological health of sportspeople and athletes due to the outbreak of COVID-19 has been reviewed in this research. This review article also analyzes the impact of COVID-19 on health mental in databases. The COVID-19 outbreak and quarantine would have a serious negative impact on the mental health of athletes. From the accessible sources, 80 research articles were selected and examined for this purpose such as Research Gate, PubMed, Google Scholar, Springer, Scopus, and Web of Science and based on the involvement for this study 14 research articles were accessed. This research has an intention on mental health issues in athletes due to the Pandemic. This report outlines the mental, emotional and behavioural consequences of COVID-19 home confinement. Further, research literature reported that due to the lack of required training, physical activity, practice sessions, and collaboration with teammates and coaching staff are the prime causes of mental health issues in athletes. The discussions also reviewed several pieces of literature which examined the impacts on sports and athletes, impacts on various countries, fundamental issues of mental health and the diagnosis for the sports person and athletes, and the afterlife of the COVID-19 pandemic for them. Because of the compulsory restrictions and guidelines of this COVID-19 eruption, the athletes of different sports and geographical regions are suffering from fewer psychological issues which were identified in this paper. Accordingly, the COVID-19 pandemic appears to negatively affect the mental health of the athletes with the prevalence and levels of anxiety and stress increasing, and depression symptoms remaining unaltered. Addressing and mitigating the negative effect of COVID-19 on the mental health of this population identified from this review.